Simple procedures for analyzing and purifying methylene green - Glusko, Carlos Abel (2012)
Methylene green is a versatile dye that can be used in a wide range of technical applications, most of which require the dye to be pure. Because commercial lots of methylene green are known to be heterogeneous, we report a thin layer chromatographic method for checking purity. We also describe a simple and effective flash chromatographic purification procedure for subsequent purification. The identity and purity of the dye can be checked easily using UV-visible absorption spectrum measurements or by more sophisticated procedures if necessary. © 2012 The Biological Stain Commission.